Profile of Learning Motivation of Students with Minang Ethnic Background and its Implication in Guidance and Counseling - Wahid, Ahmad; Neviyarni, Neviyarni; Nirwana, Herman (IKIP Siliwangi, 2025)
Good learning motivation will affect student success and achievement at school. Learning motivation is the power and drive that directs students to perform their academic responsibilities. This study was conducted to determine the learning motivation profile of students with Minang ethnic background. This study used a quantitative approach with descriptive methods. The sample in this study consisted of 99 high school students who were taken by purposive sampling. The special criteria are students with Minang ethnic background. Data was collected using a learning motivation scale with a Likert model and tested for validity and reliability. The results concluded that the learning motivation profile of students with Minang ethnic background is moderate. This outlines that Minangkabau culture has a fairly good influence on student learning motivation, where, based on the data description results, no students have low learning motivation. The implication of this research is as a reference for guidance and counseling teachers regarding the importance of paying attention to the condition of student learning motivation at school. PayingIt should be done by looking at the background and characteristics of each student.